(-3)^2 should be 9 instead of -9 as (-) * (-) = (+)

when -3 is cubed, it is not suppose to have the end result of -9, but instead 9 as negative 3 times negative 3 is a positive number.

when negative x negative = positive not negative. Owen here.

The ^2 should be outside of the bracket as it is (-3)^2 and not (-3^2) .

The error is: negative x negative = positive.(-3)^2 = 9 NOT -9

your power shld be outside the bracket because ur substituting the letter u shld bracket the letter solely

Negative x negative should be positive instead of negative.

2x^2 - x^3yIf x = -3, y = -12 x (-3)^2 - (-3)^3 x (-1)= 2 x 9 - (-27) (-1)= 18 - 27= -9

(-)*(-) should be +, so (-3)^2 should be 9, not -9. (-)*(-)*(-)= (-), and (-)*(-)= (+), so -(-3)^2= 27

Neg x Neg =positive

(-3)^2 should be 9, as (-)(-)=(+)

2(-3)^2=2(9) not (-9) because (-3)(-3)=9

2(-3^2) should be 2(-3)^2. -(-3^3)(-1) should be -[(-3^3)(-1)] instead.

The Error: (-3)^2 ≠ -9 as (-) * (-) = (+)It should be: (-3)^2 = 9

Power should be outside the bracket :D

(-3)^2=9(-3)^2=/=-9

The power should be outside of the bracket and negative + negative does not = postive

negative negative would be postive

The person should place the powers of the number outside of the brackets and he did not rewrite the expression of 2(-3)^2 into 2(-3)(-3). Thus he only work out (3^2)and leaving the answer as negative.

The Power should be outside the brackets.

(-3)^2 = 9 =.=

-3^2 is actually (-3)(-3) and negative x negative will give positive so it should be 9 D:Ishani.

(-3)^2 should be 9 instead of -9 as (-) * (-) = (+)

ReplyDeletewhen -3 is cubed, it is not suppose to have the end result of -9, but instead 9 as negative 3 times negative 3 is a positive number.

ReplyDeletewhen negative x negative = positive not negative.

ReplyDeleteOwen here.

The ^2 should be outside of the bracket as it is (-3)^2 and not (-3^2) .

ReplyDeleteThe error is: negative x negative = positive.

ReplyDelete(-3)^2 = 9 NOT -9

your power shld be outside the bracket because ur substituting the letter u shld bracket the letter solely

ReplyDeleteNegative x negative should be positive instead of negative.

ReplyDelete2x^2 - x^3y

ReplyDeleteIf x = -3, y = -1

2 x (-3)^2 - (-3)^3 x (-1)

= 2 x 9 - (-27) (-1)

= 18 - 27

= -9

(-)*(-) should be +, so (-3)^2 should be 9, not -9. (-)*(-)*(-)= (-), and (-)*(-)= (+), so -(-3)^2= 27

ReplyDeleteNeg x Neg =positive

ReplyDelete(-3)^2 should be 9, as (-)(-)=(+)

ReplyDelete2(-3)^2=2(9) not (-9) because (-3)(-3)=9

ReplyDelete2(-3^2) should be 2(-3)^2. -(-3^3)(-1) should be -[(-3^3)(-1)] instead.

ReplyDeleteThe Error: (-3)^2 ≠ -9 as (-) * (-) = (+)

ReplyDeleteIt should be: (-3)^2 = 9

Power should be outside the bracket :D

ReplyDelete(-3)^2=9

ReplyDelete(-3)^2=/=-9

The power should be outside of the bracket and negative + negative does not = postive

ReplyDeletenegative negative would be postive

ReplyDeleteThe person should place the powers of the number outside of the brackets and he did not rewrite the expression of 2(-3)^2 into 2(-3)(-3). Thus he only work out (3^2)and leaving the answer as negative.

ReplyDeleteThe Power should be outside the brackets.

ReplyDelete(-3)^2 = 9 =.=

ReplyDelete-3^2 is actually (-3)(-3) and negative x negative will give positive so it should be 9 D:

ReplyDeleteIshani.